A Model of Depressed Patient Care Though Willpower in Buddhism - Yooyen, Lamai; Dr., Phrasrivinayaphon (Journal of Dhamma for Life, 2024)
The research article aims to accomplish the following objectives: 1) examine theoretical concepts related to caring for patients with depression, 2) investigate the concept of willpower in Buddhism, and 3) integrate willpower care for patients with depression within the Buddhist context. Additionally, 4) disseminate knowledge on "A Model of Caring for Depressed Patients with Willpower in Buddhism." This qualitative research study involves an examination of Tripitaka, commentaries, textbooks, and pertinent research documents. The investigation includes 16 key informants, and data are gathered through in-depth interviews. The collected data are thoroughly analyzed and synthesized to address the specified objectives. The research outcomes are summarized to draw conclusions, provide guidelines, and generate a novel understanding of the care model for patients with depression utilizing the power of visualization. The findings are presented in a descriptive manner. The results showed that: The content of the theory of specific care for depression patients is consistent with the care of patients with medical depression and Western scientists, divided into 3 aspects: 1) in terms of Physical aspect, Waldorf’s Biological Theory, 2) in terms of Mental and Emotional aspects, utilize the Theory of Mind by Aaron Beck, 3) in terms of Social aspect, Erik H. Erickson's psychosocial theory. The principles of willpower used to help care and solve problems in caring for patients with depression in 3 aspects: 1) in terms of Physical aspect, apply the principles of willpower adherence to the five precepts 2) in terms of Mental and Emotional aspects, apply willpower and S̄mt̄hkrrmṭ̄hān (calmness meditation), 3) in terms of Social aspect, apply willpower and sangkhahavatthu 4. When the relevant principles of willpower are incorporated to address the issues faced by patients with depression across all three dimensions, it possesses the capability to alleviate depression. A consistent and prompt state of mindfulness can deter impurities, facilitating an environment where distractions are minimized, fostering a positive mood, and enabling individuals to lead a content and harmonious life within society. The body of knowledge gained from research on caring for depressive patients with willpower in Buddhism is the SETD Model. Applying the SETD Model for efficiency and effectiveness to patients with depression are as follows: S = Society of Mutual Understanding means building a society of mutual understanding, caring, helping volunteers to help patients with depression to have encouragement in treatment. and have the encouragement to help the society as a whole. E = Exercise Reduced Depression means patients must exercise to increase the release of happiness substances to the body. reduce depression. T = The truth of the mind and emotions means approaching the mind and emotions with truth. Aware of the desires that will come in with mindfulness, concentration, strong mental strength, able to solve problems well, without getting lost. D = Depress Eliminated means eliminating depression. By keeping the 5 precepts stable.